Maternal educational level, parental preventive behavior, risk behavior, social support and medical care consumption in 8-month-old children in Malmö, Sweden - Mangrio Elisabeth; Hansen Kristina; Lindström Martin; Köhler Marie; Rosvall Maria (BMC, 2011)
Abstract Background The social environment in which children grow up is closely associated with their health. The aim of this study was to investigate the relationship between maternal educational level, parental preventive behavior, parental risk behavior, social support, and use of medical care in small children in Malmö, Sweden. We also wanted to investigate whether potential differences in child medical care consumption could be explained by differences in parental behavior and social support. Methods This study was population-based and cross-sectional. The study population was 8 month-old children in Malmö, visiting the Child Health Care centers during 2003-2007 for their 8-months check-up, and whose parents answered a self-administered questionnaire (n = 9,289 children). Results Exclusive breast feeding ≥4 months was more common among mothers with higher educational level. Smoking during pregnancy was five times more common among less-educated mothers. Presence of secondhand tobacco smoke during the first four weeks of life was also much more common among children with less-educated mothers. Less-educated mothers more often experienced low emotional support and low practical support than mothers with higher levels of education (>12 years of education). Increased exposure to unfavorable parental behavioral factors (maternal smoking during pregnancy, secondhand tobacco smoke and exclusive breastfeeding <4 months) was associated with increased odds of in-hospital care and having sought care from a doctor during the last 8 months. The odds were doubled when exposed to all three risk factors. Furthermore, children of less-educated mothers had increased odds of in-hospital care (OR = 1.34 (95% CI: 1.08, 1.66)) and having sought care from a doctor during the last 8 months (OR = 1.28 (95% CI: 1.09, 1.50)), which were reduced and turned statistically non-significant after adjustment for unfavorable parental behavioral factors. Conclusion Children of less-educated mothers were exposed to more health risks, fewer health-promoting factors, worse social support, and had higher medical care consumption than children with higher educated mothers. After adjustment for parental behavioral factors the excess odds of doctor's visits and in-hospital care among children with less-educated mothers were reduced. Improving children's health calls for policies targeting parents' health-related behaviors and social support.